Ghouls gone wild [large type] - Laurie, Victoria (Laurie, Victoria. Ghost hunter mystery., 2010)
When M.J. Holliday and her friends travel to Scotland to film the first installment of their new cable TV show, they discover a body, an ancient curse and plenty of spooky action.